1990
DOI: 10.3109/02688699009000675
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the preservation of the facial nerve during acoustic surgery

Abstract: We reviewed the last 30 acoustic neuromas excised in our department and attempted to find out the factors associated with preservation of the facial and cochlear nerves. While the size of the tumour was the most important factor, vascularity and consistency were both important. Facial and cochlear nerves were preserved in 63% and 10% of the patients respectively. The importance of early diagnosis cannot be overemphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…On the other hand, the conclusions from the study may be related to the retrosigmoid approach only. Most of the authors agree that the size of the tumour, its consistency and degree of adherence between the lesion and the nerve have a major influence on facial nerve outcome [2,23,27,29,31,34]. Crucial among them is the size of the tumour [9,20,21,37].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the conclusions from the study may be related to the retrosigmoid approach only. Most of the authors agree that the size of the tumour, its consistency and degree of adherence between the lesion and the nerve have a major influence on facial nerve outcome [2,23,27,29,31,34]. Crucial among them is the size of the tumour [9,20,21,37].…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the significant impact of tumor size on surgical outcome. 2,6,[14][15][16][17][18][19][20][21][22] The AC measurement, which is conventionally how studies have reported tumor size, was a statistically significant predictor of postoperative facial nerve outcome on univariate analysis. However, on multivariate analysis, only the AB measurement (anterior tumor extension) and the EB/BF ratio (growth parallel to the IAC) remained significantly associated with facial function, suggesting that tumor dimension is as important as tumor size to facial nerve outcome.…”
Section: Effect Of Tumor Size On Facial Nerve Outcome and Extent Of Rmentioning
confidence: 99%
“…1,3,5,6,21,23,27 In surgery for acoustic neuromas, EMG neuromonitoring has become a routine tool used to identify and protect the seventh cranial nerve; however, additional postoperative facial paresis has been reported in 10 to 27% of cases, especially following excision of large tumors. 7,18,19,28,29,31 The rate of anatomical and functional preservation of the facial nerve was significantly lower in the era before standard EMG monitoring was applied routinely. 10,29 Electrical stimulation of the facial nerve during removal of large acoustic neuromas has been widely used for longer than 20 years.…”
mentioning
confidence: 98%